2006
DOI: 10.1007/s10529-006-9026-6
|View full text |Cite
|
Sign up to set email alerts
|

Response of Growth and Fatty Acid Compositions of Nannochloropsis sp. to Environmental Factors Under Elevated CO2 Concentration

Abstract: Nannochloropsis sp. was grown with different levels of nitrate, phosphate, salinity and temperature with CO 2 at 2,800 ll l )1 . Increased levels of NaNO 3 and KH 2 PO 4 raised protein and polyunsaturated fatty acids (PUFAs) contents but decreased carbohydrate, total lipid and total fatty acids (TFA) contents. Nannochloropsis sp. grew well at salinities from 22 to 49 g l )1 , and lowering salinity enhanced TFA and PUFAs contents. TFA contents increased with the increasing temperature but PUFAs contents decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
78
4
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(93 citation statements)
references
References 15 publications
9
78
4
2
Order By: Relevance
“…grown under elevated salinity. A lower degree of unsaturation of lipids at elevated NaCl concentrations was reported for the algae Dunaliella sp., Nannochloropsis sp., and N. frustulum (Renaud and Parry 1994;Xu and Beardall 1997;Hu and Gao 2006).…”
Section: Discussionmentioning
confidence: 99%
“…grown under elevated salinity. A lower degree of unsaturation of lipids at elevated NaCl concentrations was reported for the algae Dunaliella sp., Nannochloropsis sp., and N. frustulum (Renaud and Parry 1994;Xu and Beardall 1997;Hu and Gao 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Also, overproduction of neutral lipids in a mutant of C. reinhardtii under nitrogen starvation has been achieved through blocking a competing pathway to produce starch . For Nannochloropsis spp., it has been reported that nitrogen shortage can lead to significant accumulation of saturated and monounsaturated fatty acids (Hu and Gao, 2006). These fatty acids are mainly associated with storage triacylglycerols, the preferred substrate for biodiesel production.…”
mentioning
confidence: 99%
“…8,9) In recent years, various strains of Nannochloropsis have been investigated for their biomass production, lipid composition, and content under different growth conditions. 8,[10][11][12][13][14] To further develop them into an integrated photons-to-fuel production platform, high-efficiency transformation methods are necessary.…”
mentioning
confidence: 99%